1386 Does Total Parenteral Nutrition Raise Serum Vitamin D Level in Preterm Infants?. (October 2012) - Onwumeme, C; Martin, F; McCarthy, R; Kilbane, M; McKenna, MJ; Murphy, N; Molloy, EJ
Abstract : Background: Vitamin D (25OHD) plays an important role in skeletal and non skeletal health. 25OHD deficiency is common in preterm infants. Very low birth weight (VLBW) preterm infants depend entirely on total parenteral nutrition (TPN) and breast milk for their nutritional requirements during early post-natal life. Aim: To assess serum 25OHD status in VLBWs and the effect of TPN on serum 25OHD level during early parenteral nutrition. Methods: Serum 25OHD levels were evaluated by radioimmunoassay from VLBWs at birth and immediately before commencement of oral additional vitamin D supplementation. Results: 22 VLBWs were included in this study and had 44 samples taken. Their mean gestational age (SD) was 28±2 weeks and birth weight 1.2±0.4 kg. There were 11 males and 11 females, 3 Black Africans, 1 Asian, and 18 Caucasians. The number of TPN days was 12±5 and the daily intake of 25OHD3 from TPN was 118±45 IU/day. The 25OHD content in expressed breast milk was negligible. The 25OHD levels increased from 26±18 nmol/L (at birth) to 36.2±20 nmol/L (pre-vitamin D enteral supplementation)(p=0.09). The increase in 25OHD levels did not reach sufficiency (≥50nmol/L). Conclusions: Inadequate nutrition during the early days of preterm infants can lead to poor growth and increased morbidity. Total parenteral nutrition and breast milk are the predominant source of nutrition in early postnatal life of VLBWs. This study showed that vitamin D content of TPN increased 25OHD level but not up to sufficiency (≥50nmol/L).